Management of Public Sector Strategies in Dealing with the Use of Public Service Applications for People in Bangladesh - Kirmakar, Nilami (Pusat Studi Pembangunan dan Pemberdayaan, 2023)
The digital revolution has had a profound impact on public service delivery worldwide, and Bangladesh is no exception. In recent years, the government of Bangladesh has made significant strides in embracing technology to improve citizen-government interactions through public service applications. These applications offer a wide range of services, from tax payments and utility bill settlements to healthcare and education resources, making governance more accessible and citizen-centric. However, the effective management of public service applications poses several challenges, including technical issues, administrative hurdles, user-related concerns, and legal and regulatory complexities. This thesis explores the management of public sector strategies in dealing with the use of public service applications in Bangladesh. A mixed-methods research design is adopted, encompassing both qualitative and quantitative data collection methods. A literature review provides an overview of the current landscape of public service applications in the country and highlights best practices from other nations. Primary data is collected through surveys and interviews, which capture citizen perspectives and experiences, as well as insights from government officials and technology experts. The findings indicate that public service applications have a positive impact on governance, enhancing accessibility, efficiency, and transparency. However, challenges such as limited digital infrastructure, cybersecurity concerns, bureaucratic resistance, and digital literacy gaps need to be addressed. Strategies for effective management are proposed, including improving technical infrastructure, enhancing cybersecurity measures, promoting user education, streamlining administrative processes, and fostering collaboration with the private sector and NGOs. Furthermore, the importance of data privacy policies, multilingual applications, and continuous user feedback for enhancing citizen trust and inclusivity is emphasized.